The effects of work surface hardness on mechanical stress, muscle activity, and wrist postures. - Jeong Ho Kim; Aulck, Lovenoor; Trippany, David; Johnson, Peter W. (Work, 2015)
BACKGROUND: Contact pressure is a risk factor which can contribute to musculoskeletal disorders. OBJECTIVE: The objective of the present study was to determine whether a work surface with a soft, pliable front edge could reduce contact pressure, muscle activity, and subjective musculoskeletal comfort, and improve wrist posture relative to a conventional, hard work surface. METHODS: In a repeated-measures blinded experiment with eighteen subjects (8 females and 10 males), contact pressure, wrist posture, typing productivity, perceived fatigue, wrist and shoulder muscle activity, and subjective comfort were compared between the two different work surfaces during keyboard use, mouse use and mixed mouse and keyboard use. RESULTS: The results showed that across the three modes of computer work, the contact pressure was lower on the soft-edge work surface compared to the conventional work surface (p's < 0.03) and subjects reported to have less perceived fatigue in the forearms and wrists. No differences in muscle activity, wrist posture, and subjective comfort were measured between the two work surfaces. CONCLUSIONS: Given the significant reduction in contact pressure and corresponding lower ratings in perceived fatigue, the soft-edge work surface subjectively and objectively improved measures of contact stress which may reduce physical exposures associated with the onset and development of musculoskeletal disorders.